2016
DOI: 10.1057/s41267-016-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of Capitalism and institutional comparative advantage: A test and reinterpretation

Abstract: How do national-level institutions relate to national comparative advantages? We seek to shed light on this question by exploring two different sets of hypotheses based on the Varieties of Capitalism and other branches of comparative capitalisms literature. Applying fuzzy-set qualitative comparative analysis to data from 14 industries in 22 countries across 9 years, we find that comparative advantages in industries with radical innovation emerge in specific configurations mixing coordinated and liberal institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(84 citation statements)
references
References 75 publications
(92 reference statements)
4
59
0
2
Order By: Relevance
“…Empirical results of these efforts have generally produced mixed results. More recently, Witt and Jackson (2016) have suggested that complementarities may reside not in coherence, but instead in incoherent institutions forming what Streeck (1997) termed 'beneficial constraints'. While they applied this argument to the question of how radical and incremental innovation translate into comparative advantages, their overall point may generalize to other forms of institutional complementarities and attendant outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Empirical results of these efforts have generally produced mixed results. More recently, Witt and Jackson (2016) have suggested that complementarities may reside not in coherence, but instead in incoherent institutions forming what Streeck (1997) termed 'beneficial constraints'. While they applied this argument to the question of how radical and incremental innovation translate into comparative advantages, their overall point may generalize to other forms of institutional complementarities and attendant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of evolution over time, research has explored the question of convergence (Djelic, 1998;Whitley, 1999;Deakin et al, 2016), but also an apparent trend towards liberalization (Thelen, 2014;Van der Zwan, 2014) and institutional adaptability more generally (Streeck and Thelen, 2005;Vogel, 2006;Witt, 2006;Hall and Thelen, 2009;Jackson and Deeg, 2012). And with regard to outcomes, the literature has examined the linkages between varieties of capitalism and results such as comparative advantages (Hall and Soskice, 2001;Whitley, 2007;Schneider and Paunescu, 2012;Witt and Jackson, 2016), innovative capabilities (Boyer, 2004;Akkermans et al, 2009;Allen, 2013;Keller and Block, 2013;Boschma and Capone, 2015), CSR (Matten and Moon, 2008;Gjølberg, 2009;Jackson and Apostolakou, 2010;Brammer et al, 2012;Kang and Moon, 2012) and inequality (Rueda and Pontusson, 2000;Schneider and Makszin, 2014;Thelen, 2014). This list is far from exhaustive, and a comprehensive review of these efforts is beyond the possibilities even of dedicated review papers (Wood et al, 2014), leave alone research papers such as this one.…”
Section: Motivation and Epistemologymentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 1, we plot this variation (measured as the number of incoming migrants per year divided by the population) against the index of coordination devised by Witt and Jackson (2016), which captures the degree of market embeddedness we mentioned above. On average, more liberal political economies tend to receive more migrants than coordinated economies, even if the correlation between coordination and immigration levels is not very strong (r = -0.34).…”
Section: The Impact Of Migration On Models Of Capitalismmentioning
confidence: 99%